The Cambridge global history of fashion - Breward, Christopher, 1965-; Lemire, Beverly, 1950-; Riello, Giorgio, 1974- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2023)
"Over the twentieth century multi-disciplinary academic studies addressed dress practice and bodily adornment from a variety of perspectives, assessing the question of fashion, though few communities outside the West were awarded this term until the past generation. Anthropologists took an ethnographic stance, with works that from the late 1980s became more attentive to the lived significance of clothing that reflected 'agency, practice and performance' with local and global impact.1 Anthropological studies revealed how clothing resisted and critiqued imperial perspectives, including choices of bodily adornment, integral to community coherence, transforming priorities and social dynamism. These examinations, across world terrains, became richly nuanced with vital studies of evolving clothing systems, including those entangled with decolonization, political changes, and material challenges.^
Critical analyses of clothing modes opened wideranging, cross-cultural studies on the subject of dress and fashion, attentive to the dialogic relationship between colonies and metropoles and other societal forms"--
The significance of this scholarship affected other disciplinary fields, from history and art history, to cultural and museum studies, with modes of close looking and analysis, as increasing numbers of scholars explored the important matter of 'the social skin'. As Terence Turner observed: 'Decorating, covering, uncovering or otherwise altering the human form in accordance with social notions of everyday propriety or sacred dress, beauty or solemnity, status or changes in status, or on occasion of the violation and inversion of such notions, seems to have been a concern of every human society of which we have knowledge. ... the symbolic stage upon which the drama of socialization is enacted'.2 Studies of clothing revealed its variable efficacy as a tool to discipline colonized peoples, as well as a tool of resistance; while gender practices and the critical resistance of norms were also lively fields of study.^
Volume II surveys the history of fashion from the nineteenth-century to the present day. Covering the period beginning with mass industry and ending with calls for sustainability, this volume challenges the meaning of modernity and modernism from a global perspective and reflects on important scholarship that has changed our understanding of the relationship between fashion and colonialism. Empires shifted and new powers rose, with fashion marking and contending with this change. The volume concludes with a critical view of fashion and globalisation, and explores the deep connections between the fashion industry, the global economy, and the politics of production and wearing in the contemporary world.
2. From the nineteenth century to the present
Description based on online resource; title from digital title page (viewed on October 16, 2023).
Keywords: Fashion and globalization -- History; Fashion -- History; Clothing and dress -- History